The Impact Of Cost Accounting On Healthcare Quality Management - Annisya Nurul Zahra Rifta Elmid; Rifta Elmid Safitri; Dwi Noerjoedianto; Arnild Augina Mekarisce (CV. AFDIFAL MAJU BERKAH, 2026)
The transformation of the healthcare system toward Value-Based Healthcare requires efficient cost management without compromising patient quality and safety. This study aims to analyze the impact of cost accounting implementation on healthcare quality management through a systematic literature review approach. The research method follows the PRISMA 2020 guidelines, with literature searches conducted through Google Scholar, PubMed, and SINTA databases. Article selection was carried out using the PICOS framework to ensure relevance to the research objectives. The screening process resulted in nine eligible articles that were analyzed through qualitative synthesis. The findings indicate that the implementation of modern cost accounting methods, such as Activity-Based Costing (ABC), Time-Driven Activity-Based Costing (TDABC), and Itemized Point Cost (IPC), significantly contributes to improving operational efficiency, enhancing cost transparency, reducing the risk of medical errors, and supporting healthcare accreditation standards. However, excessive emphasis on strict cost control may influence patients’ perceptions of service quality. Therefore, the integration of financial and non-financial performance indicators is essential to ensure that economic efficiency aligns with continuous improvement in healthcare service quality.